2012
DOI: 10.1021/cg300961m
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and Hydrated States in 5-Nitrouracil Crystallized from Aqueous Solution

Abstract: The crystallization of 5-nitrouracil (5NU) from pure aqueous solution yields two anhydrous polymorphs and a monohydrate depending on the temperature at which the process is carried out. 5NU mimics true polymorphism in that, when retained in aqueous solution, both metastable (anhydrous) forms undergo solvent mediated phase transformations (SMPTs) into the more thermodynamically stable hydrated form as would be predicted by Ostwald's rule of stages. The phase transformations can occur either in the classical man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…A detailed description of the crystal growth of 5NU from aqueous solutions, the effects of polymorphism and the role of twinning has been given by Okoth et al 7 In the present studies; crystals of 5NU-h were thin, rhombohedral tablets (Fig. 2), with a main face of (010).…”
Section: Crystal Growth and Morphologysupporting
confidence: 52%
See 4 more Smart Citations
“…A detailed description of the crystal growth of 5NU from aqueous solutions, the effects of polymorphism and the role of twinning has been given by Okoth et al 7 In the present studies; crystals of 5NU-h were thin, rhombohedral tablets (Fig. 2), with a main face of (010).…”
Section: Crystal Growth and Morphologysupporting
confidence: 52%
“…The earlier work of Okoth et al 7 has shown that there exists a limited structural relationship between 5NU-h and 5NU-o, which simply consists of a localized molecule-molecule motif; a loose dimer, with no extended supramolecular structure or long-range ordering. This local interaction is shown in Fig.…”
Section: Structural Assessmentmentioning
confidence: 99%
See 3 more Smart Citations